2022
DOI: 10.1186/s12912-022-00900-7
|View full text |Cite
|
Sign up to set email alerts
|

How do wound care nurses structure the subjective frame on palliative wound care? A Q-methodology approach

Abstract: Background Palliative wound care is important for stability in terminal care. It addresses both the physical and psychological needs of patients and facilitates other aspects of terminal care. Appropriate competencies of nurses regarding palliative wound care can improve patient outcomes and raise their quality of life. The purpose of this study was to identify how wound care nurses structure the subjective frames regarding palliative wound care. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…No Brasil, em estudo que buscou avaliar a percepção dos enfermeiros acerca de sua formação acadêmica e qualificação profissional para a prestação de CP, desvelou uma baixa exploração da temática e de disciplinas durante todo o processo formativo do enfermeiro, já que a maioria expressiva dos entrevistados além de não possuíram disciplinas relataram nunca ter participado de programas de EPS (15) . declínio" (16) . da sobrecarga e precarização do trabalho (17) .…”
Section: Discussionunclassified
“…No Brasil, em estudo que buscou avaliar a percepção dos enfermeiros acerca de sua formação acadêmica e qualificação profissional para a prestação de CP, desvelou uma baixa exploração da temática e de disciplinas durante todo o processo formativo do enfermeiro, já que a maioria expressiva dos entrevistados além de não possuíram disciplinas relataram nunca ter participado de programas de EPS (15) . declínio" (16) . da sobrecarga e precarização do trabalho (17) .…”
Section: Discussionunclassified
“…A critical component of a nurse's competence in palliative wound care, clinical judgment goes beyond mere knowledge and requires strong decision-making skills [12,17]. As the complexity of both diseases and the nursing environment grow, so too does the demand for professional nursing services that emphasize nurses' systematic problem-solving and clinical judgment skills [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of patient-centered communication, nurses' subjectivity refers to their personal experiences, beliefs, feelings, and values that influence their approach to patients, which ultimately manifest as actions and attitudes such as empathy, respect, active listening, or shared decision making 10 . Thus, understanding nurse subjectivity can help inform strategies and interventions to enhance patient-centered communication and support nurses in providing compassionate and effective care to the end-of-life patient 11 …”
mentioning
confidence: 99%
“…10 Thus, understanding nurse subjectivity can help inform strategies and interventions to enhance patient-centered communication and support nurses in providing compassionate and effective care to the end-of-life patient. 11 Nevertheless, few studies have confirmed the subjectivity of communication of nurses caring for end-of-life patients. Therefore, this study aimed to promote the understanding of this phenomenon by confirming the subjective frame of reference for nurses' patient-centered communication with end-of-life patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation